2023
DOI: 10.1073/pnas.2302725120
|View full text |Cite
|
Sign up to set email alerts
|

Reminders, but not monetary incentives, increase COVID-19 booster uptake

Abstract: Despite substantially decreasing the risk of hospitalization and death from COVID-19, COVID-19 booster vaccination rates remain low around the world. A key question for public health agencies is how to increase booster vaccination rates, particularly among high-risk groups. We conducted a large preregistered randomized controlled trial (with 57,893 study subjects) in a county health system in northern California to test the impact of personal reminder messages and small financial incentives of $25 on booster v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A large study with 57 893 participants was conducted in a Northern California health system and found that personal reminder messages increased booster vaccination rates. 24 Among 964 870 participants in 691 820 households in Denmark, two strategies increased influenza vaccination rates. 25 26 In the USA, a study found that short video messages addressing specific COVID-19 vaccine concerns increased vaccination intentions.…”
Section: Introductionmentioning
confidence: 99%
“…A large study with 57 893 participants was conducted in a Northern California health system and found that personal reminder messages increased booster vaccination rates. 24 Among 964 870 participants in 691 820 households in Denmark, two strategies increased influenza vaccination rates. 25 26 In the USA, a study found that short video messages addressing specific COVID-19 vaccine concerns increased vaccination intentions.…”
Section: Introductionmentioning
confidence: 99%